Towards real-time 4D radiation dosimetry on an MRI-Linac. (18th November 2020) - De Deene, Y; Wheatley, M; Dong, B; Roberts, N; Jelen, U; Waddington, D; Liney, G
Abstract: 4D radiation dosimetry using a highly radiation-sensitive polymer gel dosimeter with real-time quantitative magnetic resonance imaging (MRI) readout is presented as a technique to acquire the accumulated radiation dose distribution during image-guided radiotherapy on an MRI-Linac. Optimized T 2 -weighted Turbo-Spin-Echo (TSE) scans are converted into quantitative Δ R 2 maps and subsequently to radiation dose maps. The concept of temporal uncertainty is introduced as a metric of effective temporal resolution. A mathematical framework is presented to optimize the echo time of the TSE sequence in terms of dose resolution, and the trade-off between temporal resolution and dose resolution is discussed. The current temporal uncertainty achieved with the MAGAT gel dosimeter on a 1 T MRI-Linac is 3.8 s which is an order of magnitude better than what has been achieved until now. The potential of real-time 4D radiation dosimetry in a theragnostic MRI-Linac is demonstrated for two scenarios: an irradiation with three coplanar beams on a head phantom and a dynamic arc treatment on a cylindrical gel phantom using a rotating couch. The dose maps acquired on the MRI-Linac are compared with a treatment plan and with dose maps acquired on a clinical 3 T MRI scanner. 3D gamma map evaluations for the different modalities are provided. While the presented method demonstrates the potential of gel dosimetry for tracking the dose delivery during radiotherapy in 4D, a shortcoming of the MAGAT gel dosimeter is a retarded dose response. The effect of non-ideal radiofrequency pulses resulting from limitations in the specific absorption rate or B1 -field inhomogeneity on the TSE acquired Δ R 2 values is analysed experimentally and by use of computational modelling with a Bloch simulator.